A Research on the Local Community's Assessments on the Festivals Organized in Their Own Destinations - Aydın Ünal; Baran Sinan Bayar (Cactus, 2020)
The study aims to determine the assessments of the locals living in the destination of 23rd Manavgat Peace Water Festival organized on 22-28 July 2019, which is a festival organized regularly every year in Manavgat district of Antalya province. 550 questionnaire forms prepared within this framework were delivered to the local people living in the relevant destination through face-to-face communication during the festival. The data obtained from the returned questionnaire forms and found eligible for analysis (502 questionnaires) were analyzed via the SPSS 22.0 statistical data program. The results of study suggest that the local people consider the festivals useful for their destinations (89%) and have a positive perspective (91%) on the tourists who visit their destinations. Furthermore, the dimensions of the evaluation scale of the locals for festivals on the destinations they live were identified as the positive support for the development of the festivals, negative sociocultural effects of the festivals, positive economic effects of the festivals, satisfaction for development of the festivals, and positive personal effects of the festivals. It was also determined that the local community consider the following four dimensions of study as high and positive: positive support for the development of the festivals, positive personal effects of the festivals, positive economic effects of the festivals and satisfaction for development of the festivals, consider the following dimension of the study as low and negative: socio-cultural effects of the festivals.